Taxonomic novelties and pollen morphological study in the genus Neo-uvaria (Annonaceae) - Chaowasku, Tanawat; Keßler, Paul J.a.; Punnadee, Suwit; van Der Ham, Raymond W.j.m. (Phytotaxa, 2011)
Two new species of Neo-uvaria are described from southern Thailand: Neo-uvaria sparsistellata and N. telopea. In addition, new combinations are made for two Mitrephora species from the Philippines: N. merrillii and N. viridifolia. The pollen morphology of eight Neo-uvaria species and three species of the closely related genus Enicosanthum is studied, using light, scanning electron and transmission electron microscopy. The systematic affinity of Neo-uvaria is discussed on the basis of macromorphology, pollen morphology and molecular phylogenetics. The genus Enicosanthum appears to be the closest relative of Neo-uvaria.